HUBUNGAN UKURAN PUPIL DENGAN KELAINAN REFRAKSI PADA SINDROM METABOLIK MAUPUN NON SINDROM METABOLIK PADA POPULASI DI DESA KABUPATEN MALANG - Aini, Kurrotul; Sulistyowati, Anny; Vierlia, Wino Vrieda (Majalah Oftalmologi Indonesia, 2023)
Purpose: This study aims to assess the relationships between pupil size and refractive errors in both metabolic syndrome and non-metabolic syndrome populations residing in rural areas of Malang. Methods: A descriptive study was carried out in 2019 across three villages in Malang districts. All attending participants underwent a comprehensive ocular examination, including pupil size assessment. Pupil abnormalities were defined as deviations from the normal diameter of 2-4 mm in bright light. Clinically relevant refractive errors included hyperopia (SphEq value ? 0.25 D), myopia (SphEq value ? -0.25 D), and astigmatism (cylinder ? 0.25 D). Blood samples gauged serum fasting glucose, high-density lipoprotein cholesterol, and triglyceride levels. Waist circumference, systolic, and diastolic blood pressure were measured. Metabolic Syndrome diagnosis followed the 2006 International Diabetes Foundation criteria. Participants were categorized into metabolic syndrome and non-metabolic syndrome groups. Results: The examination involved 953 participants, encompassing 944 right eyes and 942 left eyes. For the right eye, 434 eyes showed emmetropia, 252 exhibited myopia, 141 had hyperopia, and 117 presented astigmatism. Pupillary abnormalities were linked to astigmatism, but lacked significance (p = 0.893). The left eye results indicated 444 eyes with emmetropia, 244 with myopia, 138 with hyperopia, and 116 with astigmatism. Correlation with pupillary abnormalities yielded a non-significant p-value of 0.864. Pupil size outcomes in metabolic syndrome (499 eyes) and non-metabolic syndrome (454 eyes) were not significant (p = 0.649). Conclusion: Refractive error does not correlate with pupil size in metabolic syndrome and nonmetabolic syndrome.